Corporate Social Responsibility Bank Syariah Indonesia: Implementasi Praktis dan Analisis Konseptual Berdasarkan Etika Sosial Imam Al-Ghazali - Amran Suradi; Mustofa Mustofa; Muhammad Yazid (Program Studi Perbankan Syariah STAI Senori Tuban, 2026)
This study analyzes the implementation of Corporate Social Responsibility (CSR) at PT Bank Syariah Indonesia (BSI) from the perspective of Islamic social ethics based on the thought of Imam Al-Ghazali. A descriptive qualitative approach is employed using content analysis of sustainability reports, CSR policy documents, official publications, and relevant academic literature on Islamic CSR (i-CSR) and Al-Ghazali’s ethical framework. The findings indicate that BSI’s CSR is structured across five main pillars: economic empowerment, education, health, humanitarian assistance, and religious facilities, supported by the systematic distribution of zakat, infaq, sadaqah, and waqf through BSI Maslahat. Beyond philanthropic activities, BSI demonstrates a shift toward empowerment-based programs and sustainable community development. These practices reflect key ethical principles of Al-Ghazali, including honesty, trustworthiness (amanah), justice, and public welfare (maslahah), while also aligning with the objectives of Islamic law (maqāṣid al-syarī‘ah). However, the study identifies limitations in the measurement of long-term social impact. Therefore, it recommends the development of maqāṣid-based performance indicators and the integration of i-CSR frameworks into sustainability reporting to enhance accountability and transformative social outcomes.